Rainfall and runoff regime in the Golema reka watershed on the territory of the hunting ground Valnište - Kostadinov Stanimir; Stefanović Tomislav; Braunović Sonja; Bilibajkić Svetlana (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2003)
Fenced hunting ground "Valnište" covers 410 ha on the slopes of the mountain Čemernik, in the Municipality Crna Trava. The hunting ground is situated in the Golema Reka watershed. Rainfall and runoff regime in the Golema Reka watershed were researched in order to create a hydrological base with the data on rainfall, available water resources and maximal discharges. Average annual rainfall design value for the watershed is 860. 14 mm. The highest monthly rainfall occurs in June and May, and the lowest in September and October. As there are no measured data, runoff regime was determined based on the method of parameter hydrology. The following calculation results are adopted for the maximal discharge: Q1000=19,0 m3·s-1 i Q100=10,90 m3·s-1. The adopted value of mean annual specific discharge (runoff module) is MQ=16,0 l·s-1·km-2.The study results of rainfall and runoff regime in the Golema Reka watershed show that hydrological conditions are favorable for the development of hunting and hunting tourism.